Comparison of fiberoptic endoscopic examination of swallowing findings between neurogenic and non-neurogenic dysphagia patients - Puspa Zuleika; Melania Jalili; Erial Bahar; Abla Ghanie (PERHATI-KL, 2022)
ABSTRACTBackground: Dysphagia is the difficulty or discomfort on swallowing which can affects a person’s quality of life. Based on pathophysiology, dysphagia can be classified as neurogenic and non-neurogenic. One method of diagnosis is to use a flexible endoscope called the Fiberoptic Endoscopic Examination of Swallowing (FEES). The basic findings obtained from the FEES examination were standing secretion, silent aspiration, hypopharyngeal sensitivity, leakage, residue, penetration and aspiration. Objective: To compare the findings of the FEES examination between patients with neurogenic and non-neurogenic dysphagia. Method: Observational research using cross sectional design. Data collection was carried out using medical record data on 94 subjects with dysphagia who underwent FEES examination at Dr. Mohammad Hoesin Hospital Palembang from January 2019 to January 2021. Result: The most common FEES finding in neurogenic dysphagia were filtered purée residue, milk residue, and biscuit residue. In the non-neurogenic dysphagia group, the most common FEES finding was filtered purée residue. There were significant differences in FEES findings between neurogenic dysphagia and non-neurogenic dysphagia in filtered purée residue (p=0.014), rice purée residue (p=0.017), flour purée residue (p=0.007), and biscuit puree penetration (p=0.017). Conclusion: There were significant differences in FEES findings between neurogenic dysphagia and non-neurogenic dysphagia concerning residue of filtered purée, residue of rice purée, residue of flour purée, and biscuit penetration. From regression analysis, the dominant factors found in neurogenic dysphagia were filtered purée penetration, flour purée residue, biscuit penetration, and found in non-neurogenic dysphagia were flour purée penetration and biscuit puree leakage.ABSTRAKLatar belakang: Disfagia adalah kesulitan atau gangguan proses menelan, yang dapat memengaruhi kualitas hidup seseorang. Berdasarkan patofisiologinya, disfagia dapat diklasifikasikan menjadi neurogenik dan non-neurogenik. Salah satu metode diagnosis adalah dengan menggunakan Fiberoptic Endoscopic Examination of Swallowing (FEES). Temuan dasar yang diperoleh dari pemeriksaan FEES adalah standing secretion, silent aspiration, sensitivitas hipofaring, leakage, residu, penetrasi dan aspirasi. Tujuan: Membandingkan hasil pemeriksaan FEES antara pasien disfagia neurogenik dan non-neurogenik. Metode: Penelitian observasional dengan desain potong lintang. Pengumpulan data dilakukan dengan menggunakan data rekam medis pada 94 subjek disfagia yang menjalani pemeriksaan FEES di Rumah Sakit Dr. Mohammad Hoesin Palembang dari Januari 2019 hingga Januari 2021. Hasil: Temuan FEES yang paling umum pada disfagia neurogenik adalah residu bubur saring, residu susu, dan residu biskuit. Pada kelompok disfagia non-neurogenik, temuan FEES yang paling umum adalah residu bubur saring. Terdapat perbedaan yang signifikan dalam temuan FEES antara disfagia neurogenik dan disfagia non-neurogenik pada residu bubur saring (p=0,014), residu bubur nasi (p=0,017), residu bubur tepung (p=0,007), dan penetrasi bubur biskuit (p=0,017). Kesimpulan: Terdapat perbedaan yang signifikan dalam temuan FEES antara disfagia neurogenik dan disfagia non-neurogenik pada residu bubur saring, residu bubur beras, residu bubur tepung, serta penetrasi bubur biskuit. Dari analisis regresi ditemukan faktor dominan di disfagia neurogenik adalah penetrasi bubur saring, residu bubur tepung, penetrasi bubur biskuit, dan di disfagia non-neurogenik adalah penetrasi bubur tepung dan kebocoran bubur biskuit.